Effects of a 8-week velocity-based resistance training with immediate visual feedback on athletic and ice-hockey specific performance in youth elite ice-hockey players - Winkler, T. (Paris Lodron Universität Salzburg, 2021)
Ice-hockey is characterized by high intensity intermitted skating, rapid direction changes and a high-speed sprinting ability and requires explosive power for quick acceleration and overall speed. Studies indicate that juniors with a well-developed maximum strength and explosive strength ability are those most likely to continue playing at the elite level. An ice-hockey player must therefore increase tight muscle strength and relative muscle mass. The purpose of this study was to investigate the effect of a velocity-based resistance training (VBT) with immediate visual feedback over 8-weeks on athletic and ice-hockey specific performance tests. Twenty-three youth elite ice-hockey players were randomly assigned to 1 of 2 groups, velocity-based training group (VBTG, n = 11) and repetitions-to-failure training group (RTF, n = 12). A third group with the same ice-hockey experience was used as control group (CG, n = 5). Both training groups performed an 8-week resistance training program with 2 sessions a week. VBTG completed the back-squat exercise with a mean velocity of 0.7 m/s and got real-time velocity feedback at the completion of each repetition using a 3-D camera-based capture barbell velocity tracking device and customized software. In contrast RTF performed the back-squat exercise at their individual 8 repetition maximum (8RM) and got no feedback. CG did not do any resistance training. Before and after the training intervention all subjects performed a number of performance tests: (1) 8RM-test, (2) 10- and 30-m linear running sprint test (RS10, RS30), (3) vertical jump test (SJ), (4) loaded squat jump test with 20-,50- and 80% additional load of the bodyweight (LSJ20, LSJ50, LSJ80), (5) 10- and 30-m linear skating sprint test (SS10, SS30) and a (6) 5 x 10-m skating agility test (SAT5x10). From the results of the loaded squat jump test the maximum dynamic force relative to body weight (Fmax20, Fmax50, Fmax80) and the time until reaching the maximum force (tF20, tF50, tF80) were determined. VBTG showed significantly (p < 0.05) greater gains in RS30 performance than RTF and highly significant (p < 0.01) greater gains than CG. The effect size of the training effect for RS30 was found to be moderate (0.40). Only the RS30 showed differences between the groups after the training intervention. VBTG showed significant greater gains within the group for 8RM (p < 0.001), Fmax50 (p < 0.05), Fmax80 (p < 0.01), tF50 (p < 0.05), tF80 (p < 0.01) and RS30 (p < 0.001). RTF showed a significant improvement only in the 8RM (p < 0.001). CG showed no significant differences. In conclusion, velocity-based resistance training with a mean velocity of 0.7 m/s and a given velocity threshold of ± 10% seems to be an adequate method to improve maximum and explosive strength in lower body muscles. Furthermore, this training method could have a positive impact on 30-m running sprint ability but due to a low effect size, the results in RS30 must be viewed with caution. In addition, no advantages in relation to the sport-specific performance tests could be determined by the VBT protocol.